ANALYSIS OF COMMUNITY PERCEPTIONS TOWARDS THE EXISTENCE OF SATRIA BUS MASS TRANSPORTATION IN KEDIRI CITY - Pertiwi , Ananda Tria Budi; Widiyanto, Wahyu (PT. Hafasy Dwi Nawasena, 2024)
This research aims to determine public perceptions regarding free city transportation